Effect of the hybridization of social and personal responsibility model and sport education model on physical fitness status and physical activity practice - Quiñonero-Martínez, Antonio Luis; Cifo-Izquierdo, María Isabel; Sánchez-Alcaraz Martínez, Bernardino Javier; Gómez-Mármol, Alberto (Frontiers in Psychology, 2023)
Physical activity patterns, sedentary habits and obesity levels among children and teenagers are indicators of a worrying reality which has been aggravated by the COVID-19 pandemic. In this context, this study has analysed the impact that new methodologies in Physical Education have on physical health aspects. Two teaching methods, namely, Teaching Personal and Social Responsibility and Sport Education Model, were hybridized, in a Secondary School in Murcia (Spain). Controlled quasi-experimental research was completed with a sample of 76 Secondary Education students aged 12-14 (male: 32; female: 44), developing a hybridization of both models in the experimental group. The Physician-based Assessment and Counselling for Exercise (PACE) questionnaire and Eurofit and Alpha Fitness motor tests were run to collect the results. Those showed significant improvement in standing long jump and speed-agility results in the control group. In the experimental group, on the contrary, no significant improvement was registered for either test, but out-of-school physical activity rates were higher. Following this research, it is concluded that both models have positive influence on physical activity habits, but the teaching time devoted to the subject of Physical Education is not enough to improve them.